“FATHERING JAPAN” :DISKURSUS ALTERNATIF DALAM HEGEMONI KETIDAKSETARAAN GENDER DI JEPANG - Yusy Widarahesty (Jurnal Kajian Wilayah, 2018)
The phenomenon of gender gap in Japan has brought many impacts of change in Japan from the declining birth rate and including the emergence of non-profit organizations (NPO) action groups namely "Fathering Japan"(Ikumen) founded by Tatsuya Ando in 2006, which tried to present as a form of resistance ideology from the myth of "Gender Stereotypes" hegemony in Japan.Ando established the NPOto encourage present and future fathers to play a more active role in child-rearing.“The priority of traditional Japanese fathers is work ... they don't know what to do even when they come home early," said Tetsuya Ando. Thus, it is important to study this social and cultural phenomenon to understand the whole structure of Japanese non-traditional security problem that can be seen through the “Fathering Japan” as a new discourse. By using the discourse alternative approach to analyze the role of the social movement of "Fathering Japan" (Ikumen) as the resistance ideology from Japan cultural mythology, the study was conducted by using qualitative methods through the Discourse Analysis by Ernesto and Chantal Mouffe.Keywords: Fathering Japan, discourse, Non Profit Organization, gender gap, JapanAbstrakFenomena kesenjangan gender di Jepang telah membawa banyak dampak perubahan di Jepang dari tingkat kelahiran yang menurun dan termasuk munculnya  Organisasi Non Profit  (NPO) yaitu "Fathering Japan" (Ikumen) yang didirikan oleh Tatsuya Ando pada 2006, yang mencoba menyajikan bentuk ideologi perlawanan dari mitos hegemoni "Gender Stereotypes" di Jepang. Ando mendirikan NPO untuk mendorong ayah hadir di masa depan untuk memainkan peran yang lebih aktif dalam membesarkan anak. "Prioritas ayah tradisional Jepang adalah pekerjaan ... mereka tidak tahu apa yang harus dilakukan bahkan ketika mereka pulang lebih awal," kata Tetsuya Ando.Dengan demikian, penting untuk mempelajari fenomena sosial dan budaya ini untuk memahami keseluruhan struktur masalah keamanan non-tradisional Jepang yang dapat dilihat melalui "Fathering Japan" sebagai diskursus baru. Dengan menggunakan pendekatan diskursus alternatif  untuk menganalisis peran gerakan sosial "Fathering Japan" (Ikumen) sebagai ideologi perlawanan dari mitologi budaya Jepang, penelitian ini dilakukan dengan menggunakan metode kualitatif melalui Analisis Wacana oleh Ernesto dan Chantal Mouffe .Kata kunci: fathering Jepang, diskursus, NPO, ketimpangan gender, Jepang